2004
DOI: 10.17221/4333-cjas
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting goat milk yield and its composition

Abstract: ABSTRACT:The aim of the paper was to prove the accuracy of various statistical models of variance analysis for estimation of systematic factors that influence milk yield and fat and protein content in dairy goats. Data on daily milk production recorded by methods AT, AC or A4 for the population of Czech White Shorthaired Goats over 1992-2002 was used for calculations. A total of 78 736 test day from 6 234 goats were analysed. Average daily milk production was 3.09 kg with 3.72% of fat and 2.84% of protein. Var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
15
1
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 8 publications
5
15
1
2
Order By: Relevance
“…For Lacaune, there was a highly significant (P < 0.01) difference between lactations starting in February and March (1.145 vs. 1.036 kg). A lower daily milk yield found for lactations starting in January and February (Improved Valachian) is in agreement with findings of Ciappesoni et al (2004) for White Shorthaired goat, who explained this fact by poor quality feeding and change from winter to summer ration. An opposite trend in Tsigai and Lacaune (milk yield lower for lactations starting in March) is in agreement with findings of CappioBorlino et al (1997) for Valle del Belice.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…For Lacaune, there was a highly significant (P < 0.01) difference between lactations starting in February and March (1.145 vs. 1.036 kg). A lower daily milk yield found for lactations starting in January and February (Improved Valachian) is in agreement with findings of Ciappesoni et al (2004) for White Shorthaired goat, who explained this fact by poor quality feeding and change from winter to summer ration. An opposite trend in Tsigai and Lacaune (milk yield lower for lactations starting in March) is in agreement with findings of CappioBorlino et al (1997) for Valle del Belice.…”
Section: Resultssupporting
confidence: 90%
“…Differences in the first three lactations found for the remaining two breeds (less than 10%) were in accordance with findings of Gonzalo et al (1994), Christodoulou et al (1997), El-Saied et al (1998) and Margetín et al (1998). However, Cappio-Borlino et al (1997), Margetín and Milerski (2000) and Ciappesoni et al (2004) found differences in the first three lactations between 13 and 17% for Valle del Belice ewes; 11 and 15% and 18 and 25% for White Shorthaired goats kept in Slovakia and the Czech Republic.…”
Section: Resultsmentioning
confidence: 94%
“…The different levels of protein and energy response on milk yields and milk composition yields between different research reports might be due to many factors such as forage to concentrate ratio (Tufarelli et al 2009;Park et al 2010), breed and traits (Ciappesoni et al 2004). But forage to concentrate ratio in this trial might not affect milk yield and milk composition since their rations were not significantly different as shown in Table 2.…”
Section: Milk Constituents and Composition Yieldsmentioning
confidence: 79%
“…Similar results were also obtained by Croatian scientists B. Mioč et al (2008) who determined that the highest milk fat content was that of goats of the 5th and higher parities (3.47 ± 0.02%), though significant differences were not observed among goats of all parities: it fluctuated from 3.42 ± 0.02% (the third parity) to 3.47 ± 0.02% (the fifth and higher parities), respectively. During the research conducted by G. Ciappesoni et al (2004), a slight increase of the milk fat content was established depending on lactation (from 3.52% during the first parity to 3.55% during the fourth and further parities, p < 0.05). Nigerian scientists D. Zahraddeen et al (2007) determined that the fat content was highest in the third parity (5.54 ± 0.03%) followed by the second parity (4.73 ± 0.03%) and least in the first parity (4.39 ± 0.02%), whereas D. Carnicella et al (2008) determined that an insignificant but statistically higher (0.1% (p < 0.001)) milk fat content was in the case of goats of the first parity as compared to that of goats of the second, third and further parities.…”
Section: Resultsmentioning
confidence: 99%